Ecotoxicological Analyses of Springs of a Brazilian Northeast Conservation Unit - de Sousa, Elielma Lima [UNESP]; Pereira, Natália Jovita; Gomes, Janderson Bruzaca; dos Santos, Margareth Marques; Santos, Débora Martins Silva (Springer Nature, 2020)
Ecotoxicological assessment is an useful tool to evaluate toxicity of pollutants on aquatic organisms. In the present study, we evaluated the lethal effect, micronucleus frequency and histological changes in gills of fish species Danio rerio exposed to water from two sources of a Conservation Unit. We performed acute tests, Micronucleus Test in blood cells and histological analysis of gills. As results, the springs had no lethal toxic effects on the species. Nuclear alterations were present in erythrocytes in organisms exposed to water from the two sampled sites. As well, we found moderate to severe gill abnormalities generating the impairment of respiratory vital functions of these organisms. This study indicates that the water of the springs does not present lethal toxic effect but damage in gills for species from short exposure time.
Keywords: Erythrocytes; Histological changes; Toxic effect